PELATIHAN PEMBIAKAN DAN PERBANYAKAN BIBIT NATA DE COCO PADA MASYARAKAT KELURAHAN GANDUS KECAMATAN GANDUS PALEMBANG - Jaksen Jaksen; Sofiah Sofiah; Martha Aznury; Elina Margaretty (Politeknik Negeri Sriwijaya, 2021)
The aim of the community service is to provide training for starter breeding and making nata de coco. This activity is expected to provide motivation for entrepreneurship in the field of nata de coco for the Gandus community. The result of making nata de coco training, knowledge of participants including benefits and how to manufacture increased to 80-90%. Competence before practice was only around 20% and increased significantly after practice to 80%. The benefits of training and the suitability of the material provided and the video presented got a good response (85-90%). The residents' desire to retry nata de coco making and entrepreneurship was only around 60-75% of the total attendees. In the future, further training is needed such as Nata de coco production techniques, entrepreneurship training, and programmed and sustainable marketing and production management training.